Respuesta :

2 (3x - 7) = -4x - 6 + 9x - 8   Simplify 2 (3x - 7)
    6x - 14 = -4x - 6 +9x - 8    Combine like terms (-4x and 9x) (-6 and -8)
    6x - 14 = 5x - 14                 Subtract 5x from both sides
      x - 14 = -14                       Add 14 to both sides
            x = 0

Check your answer.

  2 (3x - 7) = -4x - 6 + 9x - 8        Substitute x for 0
2 (3(0) - 7) = -4(0) - 6 + 9(0) - 8   Multiply 3(0)
    2 (0 - 7) = -4(0) - 6 + 9(0) - 8   Multiply -4(0)
    2 (0 - 7) = 0 - 6 + 9(0) - 8        Multiply 9(0)
    2 (0 - 7) = 0 - 6 + 0 - 8            Subtract (0 - 7)
         2(-7) = 0 - 6 + 0 - 8             Multiply 2(-7)
            -14 = 0 - 6 + 0 - 8             Get rid of the unneccesary 0s
            -14 = -6 - 8                        Subtract (-6 - 8)
            -14 = -14

So, x = 0 .